PENGARUH INFLASI, SUKU BUNGA, INVESTASI, DAN PRODUK DOMESTIK BRUTO (PDB) TERHADAP JUMLAH UANG BEREDAR DI INDONESIA - B01108062, Marselina Ety Yulianti (Jurnal Pembangunan dan Pemerataan, 2013)
The study is titled analysis of money supply in Indonesia, the goal is to determine how much influence the variable inflation, interest rates, investment, and Gross Domestic Product (GDP) on the money supply. This study uses quantitative methods. Quantitative methods are used to examine the relationship variable variable inflation, interest rates, investment, and Gross Domestic Product (GDP) with the money supply. The data used are time series data from the 1987-2011 period in the Central Bureau of Statistics and Bank Indonesia. The results showed that the correlation (R2) between the variables of inflation, interest rates, investment, and Gross Domestic Product (GDP) has a very strong connection to the money supply, and the F-test conducted between the variables has the effect of inflation, interest rates, investment , and Gross Domestic Product (GDP) on the money supply. Whereas the t test, the variable investment and Gross Domestic Product (GDP) significantly influence the money supply, except for inflation and interest rates do not significantly affect the money supply. Based on the classical assumption that the estimates obtained regression model containing positive autocorrelation, containing muktikolinearitas, and does not contain heterocedastity. Keywords: Money Supply, Inflation, Interest Rates, Investments, and Gross Domestic Product (GDP)